Analisis dan Implementasi Interkoneksi Jaringan Komputer berbasis VPNL2TP IPSEC pada SMK TKJ di Depok - Ali Imran; April Rustianto (LPPM STT Terpadu Nurul Fikri, 2021)
The world of education, especially in Vocational School Computer and Network Engineering (TKJ) schools at Depok, requires technology to support learning and teaching activities digitally or online. Currently, schools are connected via an internet connection, but there are problems related to data security when exchanging data between schools. In this research, IT infrastructure was built relating to the interconnection of computer networks in TKJ schools at Depok to connect schools with multilevel security. The method used observation, interviews, and literature to analyze the network needed and make a design to be implemented and tested from the results of the implemented design. The results of this study were successful in connecting SMK TKJ schools at Depok with Virtual Private Network (VPN) technology based on Layer 2 Tunneling Protocol (L2TP) and IP Security optimally, which has been tested. So, I concluded that the design and implementation of L2TP and IPSec VPNs could be worked well to connect between SMK TKJ at Depok.